Characterization of the complete mitochondrial genome of Hynobius bambusicolus Wang, Othman, Qiu and Borzée, 2023 (Amphibia, Caudata, Hynobiidae) and its phylogenetic implications - Yanpin Huang; Helin Wang; Haoran Luo; Honghui Zhong; Qingxian Lin; Xiaoping Zhou (Mitochondrial DNA. Part B. Resources)
Hynobius bambusicolus (Caudata, Hynobiidae) is a recently described species, identified in 2022, and is thus not widely known. In this study, we sequenced and annotated the complete mitogenome of H. bambusicolus. The resulting mitochondrial genome is 16,406 bp in length and comprises 13 protein-coding genes (PCGs), two ribosomal RNA genes (rRNA), 22 transfer RNA genes, and a non-coding region. The base composition of the mitogenome is 33.3% A, 32.1% T, 20.8% C, and 13.8% G. The phylogenetic trees indicated that H. bambusicolus is the basal branch within the Southern Chinese Hynobius clade.